(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Pulp and paper sector is the sixth largest water polluting business in the country, one of themost contaminated sectors. Environmental friendly treatment method is required to make it more usablefor irrigation purpose. A different single isolates were screened on the basis of their degradationcapability by estimating chemical oxygen demand. The form of pulp and paper water is complicated andthus it is not possible for one isolate to easily degrade the wastewater. Therefore after the screening ofsingle isolate consortium were formulated to increase the efficiency of single isolate. The efficiency ofselected consortium was increased by optimizing the different parameters. The selected consortium at35°C temperature, 72 hrs of incubation time and 300 rpm shows the degradation up to 68.Bioremediation literal meaning is to remediate the problem completely. This treatment method is thehelping hand provided by nature. The literature shows that there is possibility of applying pulp and paperwastewater in irrigation after effective treatment. It‟s clearly demonstrates that bioremediation and its usein irrigation will increase the efficiency of the pulp and paperboard industry waste. After treatment thetreated effluent was applied for crop production and it was observed that 50 consortium treatedwastewater gave optimum growth for a crop. Therefore, it is concluded that 50 diluted effluent containssufficient nutrients for plant growth.